Gene expression analysis of membrane transporters and drug‐metabolizing enzymes in the lung of healthy and COPD subjects - Berg, Tove; Hegelund Myrbäck, Tove; Olsson, Marita; Seidegård, Janeric; Werkström, Viktoria; Zhou, Xiao‐Hong; Grunewald, Johan; Gustavsson, Lena; Nord, Magnus (Pharmacology research & perspectives, 2014)
This study describes for the first time the expression levels of genes encoding membrane transporters and drug‐metabolizing enzymes in the lungs of ex‐smoking patients with chronic obstructive pulmonary disease (COPD). Membrane transporters and drug‐metabolizing enzymes are key determinants of drug uptake, metabolism, and elimination for systemically administered as well as inhaled drugs, with consequent influence on clinical efficacy and patient safety. In this study, while no difference in gene expression was found between healthy and COPD subjects, we identified a significant regional difference in mRNA expression of both membrane transporters and drug‐metabolizing enzymes between central and peripheral tissue in both healthy and COPD subjects. The majority of the differentially expressed genes were higher expressed in the central airways such as the transporters SLC2A1 (GLUT1), SLC28A3 (CNT3), and SLC22A4 (OCTN1) and the drug‐metabolizing enzymes GSTZ1, GSTO2, and CYP2F1. Together, this increased knowledge of local pharmacokinetics in diseased and normal lung may improve modeling of clinical outcomes of new chemical entities intended for inhalation therapy delivered to COPD patients. In addition, based on the similarities between COPD and healthy subjects regarding gene expression of membrane transporters and drug‐metabolizing enzymes, our results suggest that clinical pharmacological studies in healthy volunteers could be a valid model of COPD patients regarding drug disposition of inhaled drugs in terms of drug metabolism and drug transporters. e00054